ECONOMICAL EFFECT OF ON-THE-JOB TRAINING: USING KOREAN FIRM PANEL DATA - Jung, Dae Bum (PEOPLE: International Journal of Social Sciences, 2016)
The study aims to investigate the economic effect of firm on-the-job training using a panel data in Korea, improving analysis data, method, and study model of a precedent study. To accomplish the object of this study, the panel analysis was applied to analyze using a Korea Investors Service (KIS), Human Capital Corporate Panel (HCCP) and Workplace Panel Survey (WPS) data. The results of this study show that positive effect firm on-the-job training on firm’s productivity. Based on the results of this study, government should need to make a policy development to reinforcement investment on firm on-the-job training at the national level. And it was drawn in a conclusion to need not avoid but continuous investment on firm on-the-job training at the company level.